2022
DOI: 10.1007/s10549-021-06478-z
|View full text |Cite
|
Sign up to set email alerts
|

An overview of genetic services delivery for hereditary breast cancer

Abstract: Breast cancer is the most common cancer diagnosed in women worldwide, with approximately 5–10% of cases attributed to high penetrance hereditary breast cancer (HBC) genes. The tremendous advances in precision oncology have broadened indications for germline genetic testing to guide both systemic and surgical treatment, with increasing demand for cancer genetic services. The HBC continuum of care includes (1) identification, access, and uptake of genetic counseling and testing; (2) the delivery of genetic couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 80 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…27 Genetic counselors have proven to be an integral part of care for these patients, yet there is already a national shortage of counselors in the midst of increasing demand. 26 Genetic professionals are sparse amongst rural populations, which has resulted in many tests being ordered without genetic consultation. 28 More attention is needed in expanding access to this resource for patients seen across all practice settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Genetic counselors have proven to be an integral part of care for these patients, yet there is already a national shortage of counselors in the midst of increasing demand. 26 Genetic professionals are sparse amongst rural populations, which has resulted in many tests being ordered without genetic consultation. 28 More attention is needed in expanding access to this resource for patients seen across all practice settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated higher genetic testing rates amongst patients who are referred for consultation with a genetic counselor. 25,26 On-site genetic counselors were likely a primary reason why our institutional testing rate was nearly 70%. These results merely highlight the importance of access to genetic counselors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of cancer genetic counseling in China is in its beginning. Unlike some developed countries where specialized and certified genetics health professionals are available ( 92 ), cancer genetic counseling relies heavily on clinicians. Setting up standardized workflows and training eligible counselors is pivotal for promoting genetic counseling in China.…”
Section: Genetic Counseling For Brca Mutation Carr...mentioning
confidence: 99%
“…Over 2 million new cases were diagnosed in 2018, accounting for almost 25% of cancer cases among women. Although hereditary and genetic factors account for 5-10% of BC cases [3], nonhereditary factors are more commonly involved in geographical and ethnic differences in incidence [4]. The relationship of BC with thyroid disease (TD) has been widely investigated.…”
Section: Introductionmentioning
confidence: 99%